Collecting and sharing movies' in the digital era: Audiences:practices and the sociocultural implications in the case of Taiwan - Vinnie Guo-Chiang Yu (International Telecommunications Society (ITS), 2011)
With the coming of 'multi-platform film-viewing' era, contemporary viewers can enjoy movies not only at the cinema, but also at home via innovative media technology, such as DVDs and Internet. Therefore, movies can be played and stored in different formats, from celluloid films, video tapes, to DVD discs and digital files. For many viewers, movie-collecting, along with film-viewing become of the essential parts of domestic movie-related leisure activities. However, not many existing literatures are focusing on viewers' movie-collecting activity, especially in today's digital media-rich environment, with the exception of some research about viewers' practices of video movie collecting, related activities and the meanings behind their collecting practices (Tashiro, 1996; Dinsmore, 1998; and Bjarkman, 2004). Owing to some specific characteristics of digital media like DVD discs or potable hard drives, sharing collected movies with other people becomes a popular activity for contemporary viewers to conduct. Therefore, the main purpose of this paper is to examine how modern viewer appropriate available information and communication technologies (ICT) to facilitate their practices of movie-collecting and sharing by adopting qualitative audience research method with respondents recruited from different age cohorts. After analyzing collected data, it is argued that DVD discs and downloaded movie files are used as a kind of social tool for audiences' to build up interaction with their family, friends, classmates or colleagues. Furthermore, sharing collected movies with other people is more significant than actually viewing those collected movies for many respondents participating in this research.
Keywords: 330; film audiences; DVD movies; movie-downloading; movie-collecting and sharing; domestic film-viewing culture